The benefits of oxidative stress for tissue repair and regeneration - Serras, Florenci (Fly (Austin), 2016)
Recent work has strengthened Drosophila imaginal discs as a model system for regeneration studies. Evidence is accumulating that oxidative stress drives the cellular responses for repair and regeneration. Drosophila imaginal discs generate a burst of reactive oxygen species (ROS) upon damage that is necessary for the activation of the Jun N-terminal kinase (JNK) and p38 MAP kinase signaling pathways. Moreover, these pathways are pivotal in the activation of regenerative growth. A hypothetical mechanism of how the ROS are initiated, and how repair and regeneration is activated is discussed here.